IMPLIKASI STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN DIMEDIASI OLEH KEBIJAKAN DEVIDEN DAN LITERASI KEUANGAN SEBAGAI MODERASI (PERUSAHAAN NON PERBANKAN PADA INDEKS IDX30 PERIODE 2015-2019) - Dhistianti Mei Rachmawantari; Ayu Puspitaningtyas (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aimed to evaluate factors that influenced companies value by using capital structure, dividend policy and financial literation. A number of 12 selected companies from IDX30 Index were participated in this study for 5 research years, where all data’s were evaluated by using E-views software. The findings not just shown a positive and significant effect of capital structure on companies value, but it also showed that financial literation gives a strong influence that impact to that relation. While the dividend policy have no power to mediating the relation between capital structure and companies value.